A high-sealing aluminum foil composite film for encapsulating silicon PU materials
By using aluminum foil composite film for sealing in the transportation of silicon PU materials, the problem of curing and adhesion of silicon PU caused by traditional packaging is solved, and high sealing and transportation efficiency are improved.
Patent Information
- Application Number
- CN202411323269.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-23
AI Technical Summary
In the prior art When transporting silicon PU materials, traditional iron barrel packaging causes silicon PU to cure and stick to the packaging, causing waste, and the packaging is not easy to remove, affecting transportation efficiency.
The aluminum foil composite film is used for sealing. A long-chain flame retardant is prepared by polymerizing 2-carboxyethylphenylphosphoric acid with diethanolamine, and polymerizing it with PET segment blocks to prepare a flame retardant PET film, and then hot-pressed composite with aluminum foil to form a high-sealing aluminum foil composite film.
The high sealing of silicon PU material is achieved, curing and adhesion problems caused by contact with the external environment are avoided, and safety and efficiency during transportation are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum foil composite films, in particular to a high-sealability aluminum foil composite film for encapsulating silicon PU materials. Background Art
[0002] Silicone PU is a healthy and professional elastic synthetic court surface material system that conforms to ergonomic principles and meets the needs of sports physical characteristics. It has the characteristics of a hard upper and elastic lower structure and can be directly constructed on cement or asphalt. It uses a single-component silicone-modified polyurethane to form a buffering and rebounding structure, and a two-component modified acrylic acid as a wear-resistant surface layer. It is generally used in basketball courts, badminton courts and other sports venues.
[0003] However, silicon PU will solidify quickly after contact with the external environment, so it needs to be kept highly sealed during transportation. Traditional transportation packaging methods mostly use iron barrels for packaging and transportation. Although this type of packaging has good sealing performance, it is not easy to remove the packaging and the silicon PU will solidify and stick to the iron barrel during long-term storage, resulting in some silicon PU being wasted. The present application uses a plastic barrel for loading and then uses an aluminum foil composite film for sealing, which not only effectively blocks the silicon PU from contacting the external environment, but also makes it difficult for the silicon PU to form a bonding layer with the surface of the aluminum foil composite film, making it easier to separate during use. Summary of the invention
[0004] The purpose of the present invention is to provide a highly airtight aluminum foil composite film for encapsulating silicon PU materials, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a high-sealing aluminum foil composite film for encapsulating silicon PU materials, comprising the following preparation steps:
[0007] S1. Add 2-carboxyethylphenyl hypophosphorous acid to diethanolamine (2.1 to 2.4 times the mass of 2-carboxyethylphenyl hypophosphorous acid), stir evenly, and react for 1 to 1.2 hours under a nitrogen atmosphere at a temperature of 95 to 105° C. to obtain a flame retardant solution;
[0008] S2. Add terephthalic acid to ethylene glycol at a mass ratio of 1:1.7-1.9, stir evenly, add fluorinated silanol solution, stir evenly, then add antimony trioxide and triethyl phosphate, stir evenly, at a temperature of 235-245°C, a pressure of 0.25-0.35MPa, and nitrogen protection, esterify for 1.5-2h, cool to 145-155°C after the reaction, dehydrate for 0.5-1h, add flame retardant solution after dehydration, at a temperature of 260-270°C, a pressure of 100-200Pa, carry out polycondensation for 2-2.5h to obtain flame-retardant PET;
[0009] S3. Prepare a PET film by melt extrusion, longitudinal stretching, transverse stretching, heat setting, slitting and winding the flame-retardant PET; fix the PET film on a coating machine after pretreatment, and coat it with a melamine formaldehyde / polyethylene glycol mixed solution. After coating, dry it at a temperature of 65 to 75°C for 12 to 16 hours. After drying, laminate the side of the PET film coated with the melamine formaldehyde / polyethylene glycol mixed solution with aluminum foil for hot pressing to prepare an aluminum foil composite film.
[0010] As an optimization, the fluorine-containing silanol solution includes the following preparation steps: adding (3,3,3-trifluoropropyl)triethoxysilane to ethanol with a mass of 0.9 to 0.95 times that of (3,3,3-trifluoropropyl)triethoxysilane, stirring evenly, adding 30 to 40% acetic acid solution to adjust the pH to 5.5 to 6.0, and preparing the fluorine-containing silanol solution for use.
[0011] As an optimization, the melamine formaldehyde / polyethylene glycol mixed solution comprises the following preparation steps: adding polyethylene glycol to deionized water with a mass fraction of 6 to 7 times that of the polyethylene glycol, stirring evenly, adding a hydrochloric acid solution with a mass fraction of 35 to 38% to adjust the pH to 4.5 to 5.5, and then adding melamine formaldehyde resin with a mass fraction of 0.06 to 0.07 times that of the polyethylene glycol, stirring for 1 to 1.5 hours at a temperature of 90 to 100° C., standing to room temperature, ultrasonic defoaming, and preparing a melamine formaldehyde / polyethylene glycol mixed solution for use.
[0012] As an optimization, the PET film pretreatment in S3 includes the following steps: washing the PET film with deionized water for 2 to 3 times, then placing the PET film in acetone for ultrasonic cleaning for 15 to 20 minutes, and drying it at a temperature of 70 to 75° C. for 2 to 4 hours after the ultrasonic cleaning.
[0013] As an optimization, a fluorinated silanol solution having a mass of 0.01 to 0.02 times that of terephthalic acid is added to S2.
[0014] As an optimization, antimony trioxide in an amount of 0.04 to 0.05% by mass of terephthalic acid is added to S2.
[0015] As an optimization, triethyl phosphate in an amount of 0.02 to 0.03% by mass of terephthalic acid is added to S2.
[0016] As an optimization, a flame retardant solution with a mass of 0.05 to 0.06 times of terephthalic acid is added to S2.
[0017] A highly airtight aluminum foil composite film for encapsulating silicon PU materials is prepared by any of the methods described above.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The present application prepares a long-chain flame retardant by polymerizing 2-carboxyethylphenyl hypophosphorous acid and diethanolamine in advance, and block polymerizes the long-chain flame retardant with a PET segment to prepare a flame-retardant PET, and then stretches the flame-retardant PET into a film by melt extrusion, and then coats a melamine formaldehyde / polyethylene glycol mixed solution on one side of the PET film, and then heat-presses and laminates it with aluminum foil after drying and shaping to prepare an aluminum foil composite film;
[0020] Among them, a long-chain flame retardant is prepared by 2-carboxyethylphenyl hypophosphite and diethanolamine, wherein the three elements of carbon, phosphorus and nitrogen are coexisting in the same molecular segment, and the flame retardant has good flame retardancy and thermal stability, and the flame retardant can participate in the PET copolymerization process, and the block polymerization is adopted to avoid the cumbersome process flow of the traditional layer-by-layer assembly method, and the direct copolymerization enhances the carbonization ability of the flame-retardant PET, and the carbon layer is an effective barrier that isolates the transfer of oxygen, so that the combustible gas is not easy to diffuse, so that it has good flame retardancy and anti-melting droplet properties, and fluorinated silane is also added in the copolymerization process, on the one hand, the fluorinated silane enhances the link between the two, and on the other hand, the fluorinated silane can also cooperate with the flame retardant to enhance the flame retardant effect of the flame-retardant PET;
[0021] The addition of fluorinated silane can also effectively enhance the hydrophobic and oleophobic effects of the PET film, and enhance the barrier effect of the PET film, but this also leads to a decrease in the bonding performance between the PET film and the aluminum foil. In order to solve this problem, one side of the formed PET film is specially grafted and modified, and coated with a melamine formaldehyde / polyethylene glycol mixed solution. After drying, a melamine formaldehyde-based core is formed, one side is linked to the hydroxyl group on the polyethylene glycol, and the other side is linked to the hydroxyl group on the PET film, so that the two are tightly combined. The two-layer composite effectively improves the overall barrier performance of the composite film, and the bonding performance of the PET film is improved by the linked polyethylene glycol, so that a good bonding effect is maintained between the PET film and the aluminum foil. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are provided in detail. The raw materials used in the experimental part of the following examples are as follows:
[0024] Table 1 - Raw materials used in the experimental part
[0025] name Specification factory (3,3,3-Trifluoropropyl)triethoxysilane Shanghai Aladdin Biochemical Technology Co., Ltd. Melamine formaldehyde Shanghai Aladdin Biochemical Technology Co., Ltd.
[0026] Example 1
[0027] S1. Add 2-carboxyethylphenyl hypophosphorous acid to diethanolamine (2.1 times the mass of 2-carboxyethylphenyl hypophosphorous acid), stir evenly, and react for 1 hour under nitrogen atmosphere at 95° C. to obtain a flame retardant solution.
[0028] S2, adding (3,3,3-trifluoropropyl)triethoxysilane to ethanol with a mass of 0.9 times that of (3,3,3-trifluoropropyl)triethoxysilane, stirring evenly, adding 30% acetic acid solution to adjust the pH to 5.5, and preparing a fluorinated silanol solution for use;
[0029] S3, adding polyethylene glycol to deionized water 6 times the mass of polyethylene glycol, stirring evenly, adding 35% hydrochloric acid solution with a mass fraction to adjust the pH to 4.5, and then adding 0.06 times the mass of polyethylene glycol melamine formaldehyde resin, stirring at a temperature of 90 ° C for 1 hour, letting it stand to room temperature, ultrasonic defoaming, and preparing a melamine formaldehyde / polyethylene glycol mixed solution for use;
[0030] S4. Add terephthalic acid to ethylene glycol at a mass ratio of 1:1.7, stir evenly, add 0.01 times the mass of terephthalic acid fluorinated silanol solution, stir evenly, add 0.04% antimony trioxide and 0.02% triethyl phosphate of terephthalic acid, stir evenly, at a temperature of 235°C, a pressure of 0.25MPa, and nitrogen protection, esterify for 1.5h, cool to 145°C after the reaction, dehydrate for 0.5h, add 0.05 times the mass of terephthalic acid flame retardant solution after dehydration, at a temperature of 260°C, a pressure of 100Pa, polycondense for 2h to obtain flame-retardant PET;
[0031] S5. Prepare a PET film by melt extrusion, longitudinal stretching, transverse stretching, heat setting, slitting and winding of flame-retardant PET; wash the PET film twice with deionized water, then place the PET film in acetone for ultrasonic cleaning for 15 minutes, dry it at 70°C for 2 hours after ultrasonic cleaning, fix it on a coating machine after drying, and coat it with a melamine formaldehyde / polyethylene glycol mixed solution. After coating, dry it at 65°C for 12 hours. After drying, laminate the side of the PET film coated with the melamine formaldehyde / polyethylene glycol mixed solution with aluminum foil for hot pressing to prepare an aluminum foil composite film.
[0032] Example 2
[0033] S1. Add 2-carboxyethylphenyl hypophosphorous acid to diethanolamine (2.2 times the mass of 2-carboxyethylphenyl hypophosphorous acid), stir evenly, and react for 1 hour under nitrogen atmosphere at 100° C. to obtain a flame retardant solution;
[0034] S2, adding (3,3,3-trifluoropropyl)triethoxysilane to ethanol with a mass of 0.93 times that of (3,3,3-trifluoropropyl)triethoxysilane, stirring evenly, adding 35% acetic acid solution to adjust the pH to 5.5, and preparing a fluorinated silanol solution for use;
[0035] S3, adding polyethylene glycol to deionized water with a mass fraction of 6.5 times that of polyethylene glycol, stirring evenly, adding a 36% hydrochloric acid solution to adjust the pH to 5, and then adding 0.06-0.07 times the mass of polyethylene glycol melamine formaldehyde resin, stirring at a temperature of 95°C for 1.2 hours, letting it stand to room temperature, ultrasonically defoaming, and preparing a melamine formaldehyde / polyethylene glycol mixed solution for use;
[0036] S4. Add terephthalic acid to ethylene glycol at a mass ratio of 1:1.8, stir evenly, add 0.015 times the mass of terephthalic acid fluorinated silanol solution, stir evenly, add 0.045% times the mass of terephthalic acid antimony trioxide and 0.025% times the mass of terephthalic acid triethyl phosphate, stir evenly, at a temperature of 240°C, a pressure of 0.3MPa, and nitrogen protection, esterification reaction for 1.5h, after the reaction is completed, cool to 150°C, dehydrate for 0.8h, after dehydration, add 0.055 times the mass of terephthalic acid flame retardant solution, at a temperature of 265°C, a pressure of 150Pa, polycondensation reaction for 2h, to obtain flame-retardant PET;
[0037] S5. Prepare a PET film by melt extrusion, longitudinal stretching, transverse stretching, heat setting, slitting and winding of flame-retardant PET; wash the PET film twice with deionized water, then place the PET film in acetone for ultrasonic cleaning for 15 minutes, dry it at 70°C for 2-4 hours after ultrasonic cleaning, fix it on a coating machine after drying, and coat it with a melamine formaldehyde / polyethylene glycol mixed solution. After coating, dry it at 70°C for 14 hours. After drying, laminate the side of the PET film coated with the melamine formaldehyde / polyethylene glycol mixed solution with aluminum foil for hot pressing to prepare an aluminum foil composite film.
[0038] Example 3
[0039] S1. Add 2-carboxyethylphenyl hypophosphorous acid to diethanolamine (2.4 times the mass of 2-carboxyethylphenyl hypophosphorous acid), stir evenly, and react for 1.2 hours under a nitrogen atmosphere at a temperature of 105° C. to obtain a flame retardant solution;
[0040] S2, adding (3,3,3-trifluoropropyl)triethoxysilane to ethanol with a mass of 0.95 times that of (3,3,3-trifluoropropyl)triethoxysilane, stirring evenly, adding 40% acetic acid solution to adjust the pH to 6.0, and preparing a fluorinated silanol solution for use;
[0041] S3, adding polyethylene glycol to deionized water with a mass of 7 times that of polyethylene glycol, stirring evenly, adding a 38% hydrochloric acid solution to adjust the pH to 5.5, and then adding 0.07 times the mass of polyethylene glycol melamine formaldehyde resin, stirring at a temperature of 100 ° C for 1.5 hours, letting it stand to room temperature, ultrasonic defoaming, and preparing a melamine formaldehyde / polyethylene glycol mixed solution for use;
[0042] S4. Add terephthalic acid to ethylene glycol at a mass ratio of 1:1.9, stir evenly, add 0.02 times the mass of terephthalic acid fluorinated silanol solution, stir evenly, add 0.05% times the mass of terephthalic acid antimony trioxide and 0.03% times the mass of terephthalic acid triethyl phosphate, stir evenly, at a temperature of 245°C, a pressure of 0.35MPa, and nitrogen protection, esterify for 2h, cool to 155°C after the reaction, dehydrate for 1h, add 0.06 times the mass of terephthalic acid flame retardant solution after dehydration, at a temperature of 270°C, a pressure of 200Pa, polycondense for 2.5h to obtain flame-retardant PET;
[0043] S5. Prepare a PET film by melt extrusion, longitudinal stretching, transverse stretching, heat setting, slitting and winding of flame-retardant PET; wash the PET film with deionized water for 3 times, then place the PET film in acetone for ultrasonic cleaning for 20 minutes, dry it at 75°C for 4 hours after ultrasonic cleaning, fix it on a coating machine after drying, and coat it with a melamine formaldehyde / polyethylene glycol mixed solution. After coating, dry it at 75°C for 16 hours. After drying, laminate the side of the PET film coated with the melamine formaldehyde / polyethylene glycol mixed solution with aluminum foil for hot pressing to prepare an aluminum foil composite film.
[0044] Example 4
[0045] The difference from Example 2 is only in step S4: terephthalic acid is added to ethylene glycol at a mass ratio of 1:1.7, and after stirring evenly, 0.04% times the mass of terephthalic acid antimony trioxide and 0.02% times the mass of terephthalic acid triethyl phosphate are added, and stirred evenly. The esterification reaction is carried out for 1.5 hours at a temperature of 235°C, a pressure of 0.25MPa, and nitrogen protection. After the reaction is completed, the temperature is lowered to 145°C and dehydrated for 0.5 hours. After dehydration, a flame retardant solution with a mass of 0.055 times the mass of terephthalic acid is added, and the polycondensation reaction is carried out at a temperature of 260°C and a pressure of 100Pa for 2 hours to obtain flame-retardant PET.
[0046] Example 5
[0047] The difference from Example 2 is only in step S4: adding terephthalic acid to ethylene glycol at a mass ratio of 1:1.7, stirring evenly, adding a fluorinated silanol solution in an amount of 0.01 times the mass of terephthalic acid, stirring evenly, adding antimony trioxide in an amount of 0.04% times the mass of terephthalic acid, stirring evenly, and carrying out the esterification reaction for 1.5 hours at a temperature of 235°C, a pressure of 0.25MPa, and nitrogen protection. After the reaction, the temperature is lowered to 145°C, and dehydrated for 0.5 hours. After dehydration, a flame retardant solution in an amount of 0.055 times the mass of terephthalic acid is added, and the polycondensation reaction is carried out at a temperature of 260°C and a pressure of 100Pa for 2 hours to obtain flame-retardant PET.
[0048] Example 6
[0049] The only difference from Example 2 is step S4: adding terephthalic acid to ethylene glycol at a mass ratio of 1:1.7, stirring evenly, adding 0.01 times the mass of terephthalic acid fluorinated silicone alcohol solution, stirring evenly, adding 0.04% times the mass of terephthalic acid antimony trioxide and 0.02% times the mass of terephthalic acid triethyl phosphate, stirring evenly, at a temperature of 235°C, a pressure of 0.25MPa, and nitrogen protection, the esterification reaction is carried out for 1.5h, after the reaction is completed, the temperature is lowered to 145°C, dehydrated for 0.5h, and after dehydration is completed, the temperature is 260°C and the pressure is 100Pa. Conditions, polycondensation reaction is carried out for 2h to obtain flame-retardant PET.
[0050] Example 7
[0051] The only difference from Example 2 is step S5: the flame-retardant PET is subjected to melt extrusion, longitudinal stretching, transverse stretching, heat setting, slitting and winding processes to obtain a PET film; the PET film is washed twice with deionized water, and then the PET film is ultrasonically cleaned in acetone for 15 minutes. After the ultrasonic cleaning is completed, it is dried at a temperature of 70° C. for 2 to 4 hours. After drying, the PET film is laminated with aluminum foil for hot pressing to prepare an aluminum foil composite film.
[0052] Test Example 1
[0053] Flame retardant performance test:
[0054] Since the flame retardant effect of aluminum foil does not need to be further tested, the flame retardant performance test is performed after the PET film prepared in the above embodiment is directly coated with the melamine formaldehyde / polyethylene glycol mixed solution and dried;
[0055] The limiting oxygen index was determined according to the standard GB / T 2406.2-2009, the sample size was 0.1mm×20mm×140mm, and the combustion phenomenon was recorded;
[0056] Refer to the standard GB / T 2408-2021 vertical combustion heat, the sample size is 0.1mm×20mm×140mm, record the combustion phenomenon and evaluate the combustion level.
[0057] Table 2- Flame retardant performance test data
[0058] Experiment number LOI / % Vertical combustion heat rating Example 1 35.16 V-0 Example 2 34.93 V-0 Example 3 35.13 V-0 Example 4 31.11 V-0 Example 5 19.13 V-1 Example 6 14.31 V-2 Example 7 26.33 V-1
[0059] It can be seen from the data in the above table that the vertical combustion heat level of the polyimide film in Examples 1 to 3 is maintained at V-0, but the limiting oxygen index in Example 4 decreases, mainly because no fluorinated silane is added. Fluorinated silane can also slightly improve the flame retardant properties of the PET film.
[0060] In Example 5, the vertical combustion heat rating is only V-1, mainly because the lack of triethyl phosphate leads to an imbalance of nitrogen and phosphorus elements, and the film does not achieve the maximum flame retardant effect;
[0061] The flame retardant performance in Example 6 reached the lowest, mainly because no flame retardant solution was added, resulting in a significant decrease in the final flame retardant performance;
[0062] The flame retardant properties in Example 7 are reduced mainly because the melamine formaldehyde resin that finally participates in the grafting process is not added. Melamine formaldehyde resin itself is a good flame retardant material and also acts as a link in the material. The lack of this material leads to the final flame retardant properties of Example 7.
[0063] Test Example 2
[0064] Barrier performance test:
[0065] Since the barrier performance of aluminum foil is good and no further testing is required, this performance test is only conducted on the PET film coated with the melamine formaldehyde / polyethylene glycol mixed solution and dried in the above embodiment;
[0066] Water vapor transmission rate was measured according to ASTM F-1249, with a test area of 5 cm 2 , relative humidity 90%;
[0067] The oxygen transmission rate was measured according to ASTM D3985, with a test area of 5 cm 2 , relative humidity 0%.
[0068] Table 3- Barrier performance test data
[0069] Experiment number <![CDATA[Water vapor transmission rate / (g / m 2 -day)]]> <![CDATA[Oxygen transmission rate / (cc / m 2 -day)]]> Example 1 4.37±2.6 6.36±3.1 Example 2 4.28±2.5 6.29±2.8 Example 3 4.39±3.4 6.31±3.9 Example 4 62.51±2.3 37.32±3.1 Example 5 5.62±3.7 6.21±3.3 Example 6 31.68±3.1 21.35±2.6 Example 7 107.44±3.2 126.27±3.5
[0070] From the above data, it can be seen that in Example 7, there is no coating on the surface and only a single layer is used. At this time, the water vapor permeability and oxygen permeability are both the maximum. However, after the PET surface is coated, its barrier performance instantly increases significantly. However, in Example 4, no fluorinated silanol is added and the hydrophobicity of its surface decreases. Therefore, its water vapor permeability increases significantly at this time. Subsequently, in Example 6, since no flame retardant solution is added, there may be imperfect distribution of some chain segments during the polycondensation process, resulting in gaps in some areas of the PET film, resulting in a decrease in the final barrier performance.
[0071] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a high-sealing aluminum foil composite film for encapsulating silicon PU materials, characterized in that: The method comprises the following preparation steps: S1. Add 2-carboxyethylphenyl hypophosphorous acid to diethanolamine (2.1 to 2.4 times the mass of 2-carboxyethylphenyl hypophosphorous acid), stir evenly, and react for 1 to 1.2 hours under a nitrogen atmosphere at a temperature of 95 to 105° C. to obtain a flame retardant solution; S2. Add terephthalic acid to ethylene glycol at a mass ratio of 1:1.7-1.9, stir evenly, add fluorinated silanol solution, stir evenly, then add antimony trioxide and triethyl phosphate, stir evenly, at a temperature of 235-245°C, a pressure of 0.25-0.35MPa, and nitrogen protection, esterify for 1.5-2h, cool to 145-155°C after the reaction, dehydrate for 0.5-1h, add flame retardant solution after dehydration, at a temperature of 260-270°C, a pressure of 100-200Pa, carry out polycondensation for 2-2.5h to obtain flame-retardant PET; S3. Prepare a PET film by melt extrusion, longitudinal stretching, transverse stretching, heat setting, slitting and winding the flame-retardant PET; fix the PET film on a coating machine after pretreatment, and coat it with a melamine formaldehyde / polyethylene glycol mixed solution. After coating, dry it at a temperature of 65 to 75°C for 12 to 16 hours. After drying, laminate the side of the PET film coated with the melamine formaldehyde / polyethylene glycol mixed solution with aluminum foil for hot pressing to prepare an aluminum foil composite film.
2. The method for preparing a highly airtight aluminum foil composite film for encapsulating silicon PU materials according to claim 1, characterized in that: The fluorine-containing silanol solution comprises the following preparation steps: adding (3,3,3-trifluoropropyl)triethoxysilane to ethanol with a mass of 0.9 to 0.95 times that of (3,3,3-trifluoropropyl)triethoxysilane, stirring evenly, adding acetic acid solution with a mass fraction of 30 to 40% to adjust the pH to 5.5 to 6.0, and preparing the fluorine-containing silanol solution for use.
3. The method for preparing a highly airtight aluminum foil composite film for encapsulating silicon PU materials according to claim 1, characterized in that: The melamine formaldehyde / polyethylene glycol mixed solution comprises the following preparation steps: adding polyethylene glycol to deionized water with a mass fraction of 6 to 7 times that of the polyethylene glycol, stirring evenly, adding a hydrochloric acid solution with a mass fraction of 35 to 38% to adjust the pH to 4.5 to 5.5, then adding melamine formaldehyde resin with a mass fraction of 0.06 to 0.07 times that of the polyethylene glycol, stirring for 1 to 1.5 hours at a temperature of 90 to 100° C., standing to room temperature, and ultrasonically defoaming to prepare the melamine formaldehyde / polyethylene glycol mixed solution for standby use.
4. The method for preparing a highly airtight aluminum foil composite film for encapsulating silicon PU materials according to claim 1, characterized in that: The PET film pretreatment in S3 comprises the following steps: washing the PET film with deionized water for 2 to 3 times, then ultrasonically washing the PET film in acetone for 15 to 20 minutes, and drying the film at a temperature of 70 to 75° C. for 2 to 4 hours after ultrasonic washing.
5. The method for preparing a highly airtight aluminum foil composite film for encapsulating silicon PU materials according to claim 1, characterized in that: A fluorine-containing silanol solution in an amount of 0.01 to 0.02 times the mass of terephthalic acid is added to S2.
6. The method for preparing a highly airtight aluminum foil composite film for encapsulating silicon PU materials according to claim 1, characterized in that: Antimony trioxide is added to the S2 in an amount of 0.04 to 0.05% by mass of terephthalic acid.
7. The method for preparing a highly airtight aluminum foil composite film for encapsulating silicon PU materials according to claim 1, characterized in that: Triethyl phosphate in an amount of 0.02 to 0.03% by mass of terephthalic acid is added to S2.
8. The method for preparing a highly airtight aluminum foil composite film for encapsulating silicon PU materials according to claim 1, characterized in that: A flame retardant solution having a mass of 0.05 to 0.06 times that of terephthalic acid is added to S2.
9. A highly airtight aluminum foil composite film for encapsulating silicon PU materials, characterized in that: Prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for fluorine silicon phosphorus-containing anti-dropping flame-retardant polyethylene terephthalate
CN102391488A
Preparation method of flame-retardant linear copolyester resin
CN102660009A